Characterization of Nicotinamidases: Steady-State Kinetic Parameters, Class-wide Inhibition by Nicotinaldehydes and Catalytic Mechanism - French, Jarrod B. (2010)
Nicotinamidases are metabolic enzymes that hydrolyze nicotinamide to nicotinic acid. These enzymes are widely distributed across biology, with examples found encoded in the genomes of Mycobacteria, Archaea, Eubacteria, Protozoa, yeast and invertebrates but there are none found in mammals. Although recent structural work has improved understanding of these enzymes, their catalytic mechanism is still not well understood. Recent data shows that nicotinamidases are required for growth and virulence of several pathogenic microbes. The enzymes of Saccharomyces cerevisiae, Drosophila melanogaster and Caenorhabditis elegans regulate lifespan in their respective organisms, consistent with proposed roles in the regulation of NAD(+) metabolism and organismal aging. In this manuscript, the steady state kinetic parameters of nicotinamidase enzymes from C. elegans, S. cerevisiae, Streptococcus pneumoniae (a pathogen responsible for human pneumonia), Borrelia burgdorferi (the pathogen that causes Lyme Disease) and Plasmodium falciparum (responsible for most human malaria) are reported. Nicotinamidases are generally efficient catalysts with steady state k(cat) values typically exceeding 1 s(−1). The K(m) values for nicotinamide are low and are in the range from 2 – 110 µM. Nicotinaldehyde was determined to be a potent competitive inhibitor of these enzymes, binding in the low µM to low nM range for all nicotinamidases tested. A variety of nicotinaldehyde derivatives were synthesized and evaluated as inhibitors in kinetic assays. Inhibitions are consistent with reaction of the universally conserved catalytic Cys on each enzyme with the aldehyde carbonyl carbon to form a thiohemiacetal complex which is stabilized by a conserved oxyanion hole. The S. pneumoniae nicotinamidase can catalyse exchange of (18)O into the carboxy oxygens of nicotinic acid with (18)O-water. The collected data, along with kinetic analysis of several mutants, allowed us to propose a catalytic mechanism that explains nicotinamidase and nicotinic acid (18)O exchange chemistry for the S. pneumoniae enzyme involving key catalytic residues, a catalytic transition metal ion and the intermediacy of a thioester intermediate.